In Situ Scattering Studies of Superconducting Vacancy‐Ordered Monoclinic TiO Thin Films - Merve Baksi; Hawoong Hong; Divine P. Kumah (Advanced Physics Research, 2024)
Abstract The structural and transport properties of vacancy‐ordered monoclinic superconducting titanium oxide (TiO) thin films grown by molecular beam epitaxy are investigated. The evolution of the crystal structure during growth is monitored by in situ synchrotron X‐ray diffraction. Long‐range ordering of Ti and O vacancies in the disordered cubic phase stabilizes the vacancy‐ordered monoclinic TiO phase. The reduced structural disorder arising from vacancy‐ordering is correlated with a superconductor‐metal transition (SMT) in contrast to the superconductor‐insulator transition (SIT) observed in cubic TiO, orthorhombic Ti2O3, and the Magneli γ − Ti3O5 and γ − Ti4O7 phase. Magnetoresistance measurements for the SIT phases indicate superconducting fluctuations persisting in the normal phase. These results confirm the role of disorder related to Ti and O vacancies and structural inhomogeneity in determining the electronic properties of the normal state of titanium oxide‐based superconductors.